Governmental, Entrepreneurial and Social Dysfunctions and Responsibilities in Terms of Tourism Development Strategy Implementation in Greece: Quo Vadis? - Nousia, Aglaia; Katsoni, Vicky; Sdrolias, Labros; Velander, Kathy; Xyz, Alina; Belias, Dimitrios; Škodová Parmová, Dagmar; Dvořáková Líšková, Zuzana; Rolínek, Ladislav; Koffas, Stefanos; Kyriakou, Dimitrios (Springer International Publishing, 2018)
Greece is undoubtedly a country with a prominent tourism identity and a long –living tourism tradition. But while it is expected from its tourism sector that by the end of the next decade its total contribution to the country’s GDP and to employment in total will be huge, the weight that ought to have been given to it has not been awarded over time. The governmental strategies that were developed were circumstantial, fragmentary, lacking vision and prospect. On the other side, the local communities themselves as well as the tourist enterprises didn’t invest, as they should have, on quality, but merely on the opportunistic model of the three S “sun, sea, sand”, which, however, decayed through time lapse and cannot function anymore within the contemporary conditions of the international tourist market, where competition, mainly from the neighboring countries that offer an almost “similar” product, is intense and tough. Thus, today in the Greece of economic crisis, the need for taking all those strategic initiatives and actions so that this country manages to face the challenge of contemporary tourism, seems to be more imperative than ever before, since it will allow it to set its foot on a firm basis and stand out within a particularly complex and completely competitive setting, offering quality services and multiple differentiated choices that will satisfy the tourists’ desires and needs.
Keywords: Tourism; Environmental obstacles and dysfunctions; Corporate social responsibility; Development strategies; Greece